Redesain Dan Analisa Kelayakan PLTMH 25 KW Desa Susuan Karangasem Bali - Budiantara, Dewa Nyoman Tri; Kumara, I Nyoman Satya; Giriantari, I.A.D (Majalah Ilmiah Teknologi Elektro, 2019)
Abstract—The need for electricity in Indonesia has always increased from year to year. In Indonesia, the use of fossil power plants is still widely used. Water energy itself is an alternative to replace fossil fuels in general, one of which is a Micro Hydro Power Plant. This research was made to identify MHP in Sususan Karangasem Village can be revitalized (rebuilt) through the measurement and calculation of the potential of water resources with the flow duration curve method with a probability exceeding 80%. To analyze the feasibility of PLTMH financial analysis is carry out namely Net Present Value (NPV), Internal Rate Ratio (IRR), Payback Period (PP) and Benefit Cost Ratio (BCR). The results of the analysis found that the potential of the current Karangasem MHP is 25.18 kWh with annual electricity generation of 220.577 kWh / year and electricity BPP = Rp. 774. per kWh. From the results of the analysis, the MHP of Susuan Karangasem Village can be sayto be feasible for revitalization. Keywords: Micro Hydro Power Plant (MHP), Hydrological Analysis, Energy Economy Analysis, Revitalization.